Kontrola budżetu projektu europejskiego – znaczenie i konsekwencje - Filipiak, Beata (The control of the budget of the European project – a management approach, 2008)
The article presents the meaning of control of a budget of the European project in the decision process. The author discusses a procedure of the cost control in the internal control approach and the range of the external control. The paper describes consequences of results of external and internal control. In the last part, the author presents the meanings of the control in the process of a financial decisions making.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 67-94